The Problem of Religious Thought in Indonesia and The Paradigm of Tafsir Ilmi as One of A Solution in The Future - Rizki Firmansyah (Al-Misbah (Jurnal Islamic Studies), 2022)
In the last few years, Indonesia has been hit with a lot of issues. One of the potentially bad is the extremist image that exists in Islam. The Qur'an as a guided book of Muslims is often misunderstood but at the same time a solution of religious thought, One of them is by pointing it on the scientific side. This research is qualitative research with data taken from library observations, especially from the substance of writing and the presence of interpretation itself and other research related to current themes and issues. Therefore the approach in this study uses a text analysis approach. The conclusion of this study found that the concepts and values that exist in the interpretation of ilmi can be valuable in the future for the change and progress of society many in terms of faith and progress of thought.